DEVELOPING INTERACTIVE LEARNING MEDIA FOR SCHOOL LEVEL MATHEMATICS THROUGH OPEN-ENDED APPROACH AIDED BY VISUAL BASIC APPLICATION FOR EXCEL - Euis Eti Rohaeti; Martin Bernard; Restu Bias Primandhika (Journal on Mathematics Education, 2019)
This research is a merged descriptive and quasi-experiment research aimed to describe students’ creativity in developing interactive learning media with Visual Basic Application for Excel. Besides that, it had done to review students’ ability which learning used open-ended Visual Basic Application for Excel compared with the other students’ which learning used the expository method with Visual Basic Application for Excel based. The subject contained 35 students in experiment class and 33 students in the control class, where the creativity of their learning media is reviewed and is analysed using SPSS. The research result shows that: (1) Students’ creativity in creating interactive learning media that the learning used open-ended Visual Basic Application for Excel based is better than the one with expository method of Visual Basic Application for Excel found; (2) Students creativity in creating interactive learning media is the combination of their mastery towards school level mathematics and the ability in applying Visual Basic Application for Excel.